Model for Dimensioning Technology and Capacity of Border Railway Stations - Dimanoski, Kire; Stojić, Gordan; Vesković, Slavko; Tanackov, Ilija (Promet - Traffic&Transportation, 2012)
The participation of the national rail networks in the European corridors requires certain modifications and their redefinition. Because the railway stations are special parts of the railway networks, they should be modernized, especially in south-eastern Europe. The main issue in the process of construction or reconstruction of railway stations is dimensioning (projection) of infrastructure facilities. The dimensioning of the infrastructure capacity is in direct correlation with the projected technology of work and the planned volume of traffic. This paper presents the simulation model which allows sizing facilities of border rail stations on the basis of the defined work and traffic technology.